VOCAL RHYTHM - Khashan, Yasmeen Noury Thamer; Salman, Widad Yaqoub (Journal of Ecohumanism, 2025)
The vocal rhythm is fundamentally connected to the emotional state, and is considered an internal vocal harmony that stems from the musical agreement between the words and their meanings at times, or the words with each other at other times. The writer cannot achieve his music with the external vocal rhythm alone, so he evokes the hidden rhythm of the text, which represents the spirit and vitality of the text. Its importance lies in the integration of the text’s systems in a way that cannot be ignored, and it also works to spread internal and vocal harmony.The vocal rhythm is created by (the writer’s choice of words and the harmony between them in letters and vowels). It is also formed through the formation of words, their phonetic structure and their expressive, suggestive, and semantic characteristics. The rhythm appears, which grows and cooperates with others within the text until it produces a meaning for us. For (rhythm here is a movement that grows and generates meaning). It produces the process of conveying the idea to the recipient